2020
DOI: 10.1039/c9ta02246e
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous solution synthesis of Na3SbS4–Na2WS4 superionic conductors

Abstract: We report a facile synthetic protocol from aqueous solution for Na3SbS4-Na2WS4 superionic conductors with sodium-ion conductivity of 4.28 mS cm−1 at 25 °C, which is the highest one in reported sulfide electrolytes prepared via liquid-phase methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…It should be noted that after the completion of this study a considerably higher ionic conductivity of 32 mS cm À1 has just been reported in highly W-doped Na 3 SbS 4 . 39,40 Despite the structural similarities to Na 3 SbS 4 , tetragonal Na 4 SnS 4 (space group P42 1 c) is practically insulating with an ionic conductivity o10 À4 mS cm À1 . 41 Inspired by the then record high conductivity of LGPS 3 and the related Li 10 MP 2 S 12 family of compounds (M = Ge, Si, Sn) [7][8][9][10][11] the existence of isostructural Na 10 MP 2 S 12 (M = Si, Ge, Sn) was predicted by first-principle calculations as metastable phases with the same tetragonal space group P4 2 /nmc adopted by LGPS.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that after the completion of this study a considerably higher ionic conductivity of 32 mS cm À1 has just been reported in highly W-doped Na 3 SbS 4 . 39,40 Despite the structural similarities to Na 3 SbS 4 , tetragonal Na 4 SnS 4 (space group P42 1 c) is practically insulating with an ionic conductivity o10 À4 mS cm À1 . 41 Inspired by the then record high conductivity of LGPS 3 and the related Li 10 MP 2 S 12 family of compounds (M = Ge, Si, Sn) [7][8][9][10][11] the existence of isostructural Na 10 MP 2 S 12 (M = Si, Ge, Sn) was predicted by first-principle calculations as metastable phases with the same tetragonal space group P4 2 /nmc adopted by LGPS.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the initial report on b-Li 3 PS 4 synthesized using tetrahydrofuran (THF), 11 there have been several investigations of the liquid-phase syntheses of various solid electrolytes such as b-Li 3 PS 4 , [12][13][14] Li 7 P 3 S 11 , [15][16][17][18] Li 7 P 2 S 8 I, 19,20 Li 6 PS 5 X (X ¼ Cl, Br, I, BH 4 ), [21][22][23][24][25][26] and Na 3 MS 4 (M ¼ P, Sb). [27][28][29][30][31][32][33] In particular, we have focused on the liquid-phase synthesis of argyrodite electrolytes via solutions because of their high applicability. By using bi-solvents of THF and ethanol (EtOH), argyrodite electrolytes were synthesized through a simple solution process.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the Na3PS4 structural archetype has proven to be a fertile playground for materials design through elemental substitutions, defining a wider materials family of the general composition Na3PnCh4 (Pn: pnictogens P, As, Sb; Ch: chalcogens S, Se) 16,17,[26][27][28][29][30][18][19][20][21][22][23][24][25] ; receptive to various aliovalent substitutions, e.g. Ca 2+ on the sodium sites 31 , Clon the chalcogenide site i [32][33][34][35] , and Si 4+ or W 6+ on the pnictide site [36][37][38][39][40][41][42][43][44] . Notable compositions of the Na3PS4 structural family include Na3SbS4 with a room-temperature conductivity of the order of 10 -3 S/cm and distinct stability against ambient moisture 20,21,30 , and the recently reported tungsten-doped Na3-xWxSb1-xS4 with room-temperature Na + -conductivity of the order of 10 -2 S/cm 39,40 , currently the highest reported among polycrystalline Na + and Li + conductors.…”
mentioning
confidence: 99%